An Examination of Failed Grocery Store Interventions in Former Food Deserts. (October 2019) - Engler-Stringer, Rachel; Fuller, Daniel; Abeykoon, A. M. Hasanthi; Olauson, Caitlin; Muhajarine, Nazeem
Background . Implementing food stores in deprived neighborhoods to improve access to healthy food is a debated topic. Aims . To uncover important contributors to the closure of grocery store interventions in urban food deserts. Method . We systematically reviewed both peer-reviewed and gray literature for publications on the failure of grocery store interventions. Results . We found nine articles on six different failed food stores. The reasons stated for closure included low sales, a lack of food retail experience, poor marketing, and difficulty in attracting and retaining a high volume of consumers from the local market. Discussion . Current literature on the topic of the closure of inner-city grocery stores does not have a concise rationale to explain why inner-city grocery store interventions were not successful. Conclusion . We must consider the most appropriate interventions to improve food environments in food deserts using local and national policies to address the social determinants of health.